Answer:
What is the question?
Step-by-step explanation:
Answer:
c
Step-by-step explanation:
252 = 7 *36
36 = 6 *6 = 6²
a² -b² = (a + b)(a - b)
7h² - 252k² = 7(h² - 36k²)
= 7(h² - [6k]² )
= 7(h +6k)(h - 6k)
Answer:
12
Step-by-step explanation:
It has been going down by 6 because 24-6=18 and 18-6=12.
From the identity:
![sec(x)= \frac{1}{cos(x)}](https://tex.z-dn.net/?f=sec%28x%29%3D%20%5Cfrac%7B1%7D%7Bcos%28x%29%7D%20)
![f(x)=sec(x)= \frac{1}{cos(x)}](https://tex.z-dn.net/?f=f%28x%29%3Dsec%28x%29%3D%20%5Cfrac%7B1%7D%7Bcos%28x%29%7D%20)
the inverse of f is g such that f(g(x))=x,
we must find g(x), such that
![\frac{1}{cos[g(x)]}=x](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7Bcos%5Bg%28x%29%5D%7D%3Dx%20)
thus,
![cos[g(x)]= \frac{1}{x}](https://tex.z-dn.net/?f=cos%5Bg%28x%29%5D%3D%20%5Cfrac%7B1%7D%7Bx%7D%20)
![g(x)=cos^{-1} (\frac{1}{x})](https://tex.z-dn.net/?f=g%28x%29%3Dcos%5E%7B-1%7D%20%28%5Cfrac%7B1%7D%7Bx%7D%29%20)
Answer: b. g(x)=cos^-1(1/x)